Resveratrol-Loaded Versatile Nanovesicle for Alopecia Therapy via Comprehensive Strategies - Zhang X; Hao J; Lu T; Dong Y; Sun Y; Yu Y; Li S; Yu S; Hu H (International Journal of Nanomedicine)
Xuefei Zhang,1,2 Jiabao Hao,1 Tianli Lu,1 Yating Dong,1 Yingying Sun,1 Yingjun Yu,1 Shuxuan Li,1 Shihui Yu,1,3,4 Haiyan Hu1,3,4 1School of Pharmaceutical Sciences, Sun Yat-Sen University, Guangzhou, Guangdong Province, People’s Republic of China; 2School of Traditional Dai-Thai Medicine, West Yunnan University of Applied Sciences, Jinghong, Yunnan Province, People’s Republic of China; 3State Key Laboratory of Anti-Infective Drug Discovery and Development, School of Pharmaceutical Sciences, Sun Yat-sen University, Guangzhou, Guangdong Province, People’s Republic of China; 4Guangdong Provincial Key Laboratory of Chiral Molecules and Drug Discovery, Sun Yat-Sen University, Guangzhou, Guangdong Province, People’s Republic of ChinaCorrespondence: Haiyan Hu, Email lsshhy@mail.sysu.edu.cnIntroduction: Alopecia is a systemic disease with multiple contributing factors. Effective treatment is challenging when only hair growth mechanisms are targeted while ignoring the role of maintaining hair follicle microenvironment homeostasis, which is crucial for cell growth and angiogenesis. Oxidative stress and inflammation are major disruptors of this microenvironment, leading to inhibited cell proliferation and compromised hair follicle circulation. Drugs with antioxidant and anti-inflammatory effects could potentially restore microenvironment homeostasis, offering a promising strategy for alopecia treatment.Methods: Resveratrol (RES), a potent antioxidant and anti-inflammatory agent, was selected as the model drug and encapsulated into an active carrier—PPD-Lip to create PPD-Lip@RES. The efficacy of PPD-Lip@RES was comprehensively evaluated in both in vitro and in vivo aspects, and its underlying mechanism was also primarily explored.Results: PPD-Lip@RES promoted the proliferation and migration of dermal papilla cells, up-regulated the expression of positive hair growth regulators, and facilitated angiogenesis. It also activated hair follicle stem cells by increasing the expression of Ki67, K5, β-catenin, CD31, and CK19. In the telogen effluvium model, PPD-Lip@RES resulted in more robust hair regeneration, with less hair shedding compared to the minoxidil group. Furthermore, it showed significant therapeutic effects in severe androgenetic alopecia, outperforming finasteride and even the healthy control group.Conclusion: The results suggested that PPD-Lip@RES, as a systemic intervention strategy, could effectively facilitate hair growth by targeting both the pathological and physiological processes involved in hair loss. Its superior performance in both telogen effluvium and androgenetic alopecia models indicates its potential as an advanced treatment option for alopecia.Keywords: hair loss, microenvironment, antioxidant, anti-inflammatory, nanocarrier